Rebudgeting: Scope, triggers, players - Eugenio Anessi-Pessina; Mariafrancesca Sicilia; Ileana Steccolini (Budgetary Research Review (BRR), 2013)
The current crisis of public finances and the context of austerity require a rethinking of governmental budgets' roles, processes, and contents. On the one hand, increasing pressures exist to cut back expenditure and reduce the amount of accumulated public debt. On the other, governments are required to respond to citizen expectations and pursue economic growth. Public budgets are central to such trends, but are experiencing a significant change in the way they are conceived, used, perceived by players.
Keywords: 330